FAKTOR YANG MEMENGARUHI NILAI PERUSAHAAN DENGAN MEDIASI KINERJA PERUSAHAAN PADA PERUSAHAAN PROPERTI - Micheal; Wijaya, Henryanto (Jurnal Paradigma Akuntansi, 2025)
This study aims to obtain empirical evidence about the effect of capital structure, institutional ownership, and managerial ownership on firm value with firm performance as mediation in property sector companies listed on the Indonesia Stock Exchange for the period 2019 to 2021. The sampling method used was purposive sampling thus 51 sample companies were obtained. Data processing is carried out using the SmartPLS 4.0.8.4 program. The results of this study indicate that capital structure, institutional ownership, and managerial ownership do not have a significant effect on firm value, and firm performance does not mediate the relationship between capital structure, institutional ownership, and managerial ownership on firm value. The implication of this research is that investors need to pay attention to external factors such as the global economic situation, investor sentiment, and capital market conditions to be able to measure a company's value more accurately.